Staff perspectives on the influence of patient characteristics on alarm management in the intensive care unit: a cross-sectional survey study - Felix Balzer; Louis Agha-; Nicole Ziemert; Malte Schmieding; Lina Mosch; Mona Prendke; Maximilian Markus Wunderlich; Belinda Memmert; Claudia Spies; Akira-Sebastian Poncette (BMC, 2023)
Abstract Background High rates of clinical alarms in the intensive care unit can result in alarm fatigue among staff. Individualization of alarm thresholds is regarded as one measure to reduce non-actionable alarms. The aim of this study was to investigate staff's perceptions of alarm threshold individualization according to patient characteristics and disease status. Methods This is a cross-sectional survey study (February-July 2020). Intensive care nurses and physicians were sampled by convenience. Data was collected using an online questionnaire. Results Staff view the individualization of alarm thresholds in the monitoring of vital signs as important. The extent to which alarm thresholds are adapted from the normal range varies depending on the vital sign monitored, the reason for clinical deterioration, and the professional group asked. Vital signs used for hemodynamic monitoring (heart rate and blood pressure) were most subject to alarm individualizations. Staff are ambivalent regarding the integration of novel technological features into alarm management. Conclusions All relevant stakeholders, including clinicians, hospital management, and industry, must collaborate to establish a "standard for individualization," moving away from ad hoc alarm management to an intelligent, data-driven alarm management. Making alarms meaningful and trustworthy again has the potential to mitigate alarm fatigue - a major cause of stress in clinical staff and considerable hazard to patient safety. Trial registration The study was registered at ClinicalTrials.gov (NCT03514173) on 02/05/2018.